2021
DOI: 10.1002/chem.202100560
|View full text |Cite
|
Sign up to set email alerts
|

A Protecting‐Group‐Free Synthesis of (−)‐Salvinorin A

Abstract: A concise enantioselective total synthesis of the neoclerodane diterpene (À )-salvinorin A is reported. The stereogenic center at C-12 was installed by catalytic asymmetric propargylation with excellent enantioselectivity, and the remaining six stereogenic centers were set up highly diastereoselectively under substrate control. As for our previous synthesis of racemic salvinorin A, two intramolecular Diels-Alder reactions were applied to generate the tricyclic core. A chemoselective Mitsunobu inversion of a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Owing to its wide medicinal importance, various research groups have reported different routes for its synthesis. Recently, in 2021, Zimdar et al [ 52 ] devised an efficient strategy for the total synthesis of salvinorin. The total synthesis was initiated with the synthesis of lactone via a number of steps resulting in the generation of lactone 60 in 87% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Owing to its wide medicinal importance, various research groups have reported different routes for its synthesis. Recently, in 2021, Zimdar et al [ 52 ] devised an efficient strategy for the total synthesis of salvinorin. The total synthesis was initiated with the synthesis of lactone via a number of steps resulting in the generation of lactone 60 in 87% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Prior syntheses and medicinal chemistry campaigns struggled with the configurational lability of C8, which underwent epimerization ( K eq = 2.5) to generate the low potency 8 -epi -SalA under acidic, basic, and thermal conditions . Whereas total syntheses might provide more analogs for property optimization, they have ranged from 16–29 steps (1.3–0.3% yield) generated no analogs and retained, by definition, the C8 configurational lability of SalA itself . As a result, two syntheses targeted stabilized SalA scaffolds that would not epimerize.…”
Section: Introductionmentioning
confidence: 99%
“…Prior syntheses [14][15][16][17][18][19][20] and medicinal chemistry campaigns struggled with the configurational lability of C8, which underwent epimerization (Keq = 2.5) to generate the low potency 8-epi-SalA under acidic, basic and thermal conditions. 5 Whereas total syntheses might provide more analogs for property optimization, they have ranged from 16-29 steps (1.3-0.3% yield) [14][15][16][17][18][19][20][21][22] generated no analogs and retained, by definition, the C8 configurational lability of SalA itself. 22 As a result, two syntheses targeted stabilized SalA scaffolds that would not epimerize.…”
mentioning
confidence: 99%
“…Prior binding models suggested a hydrogen bond in this region as necessary for high potency; 57 a recent furan-tophenyl replacement retained affinity but lost potency. 24 To probe in-plane hydrogen bonding, we replaced the 3-furyl with strong acceptors 58 like 3-and 4-pyridyl (20)(21), but these led to potency losses (Figure 4C). Instead, 3-thiophenyl (19) and phenyl (25a) led to increased potency, which might have suggested important cation-π or π-π interactions 59 perpendicular to the plane of the electron-rich rings.…”
mentioning
confidence: 99%